Improvement of Gel Properties of Salt-Reduced Fish Sausage by Adding Food Additives - Do, Thi Yen; Nguyen, Thi Dieu Trang; Nguyen, Thi Thanh Ngoan (Engineering and Technology For Sustainable Development, 2024)
Low-salt seafood products are gaining popularity for their lower health risks, while the food industry faces technical challenges in improving its quality. In Vietnam, an average of 100g of sausage contains 1.5g of NaCl, equivalent to 600 mg of sodium, nearly half of the recommended daily salt intake and 2/3 of the sodium needs of children from 4 to 6 years old. This study aimed to assess the effect of sodium chloride (NaCl) reduction on texture of fish sausages and improve their texture by food addivities. Fish sausage were manufactured by blending surimi with different concentrations of four food addtivies and other ingredients, and the quality characteristics were evaluated. The gel strength of fish sausage reduced with reduction of salt concentration. egg white powder (EW), whey protein concentrate (WPC), kappa carrageenan (κ-carrageenan), transglutaminase (TGase) are effective in improving the texture of reduced-salt sausages. The addition of 1% EW and 1% WPC, 09% κ-carrageenan and 0.3% TGase results in the gel strength of sausage increasing to 1.25- time. In particular, a 0.9% κ-carrageenan and 0.3% TGase added sausage exhibited the higher gel strength and water holding capacity among the sausages.